Production and recovery of lignin peroxidase from Pleurotus Pulmonarius (Fr) quel by aqueous two phase system / Nooshin Mohebali - Mohebali, Nooshin (2014)
Pleurotus pulmonarius is an edible mushroom, which secretes lignocellulolytic enzymes, like laccase and lignin peroxidases. These enzymes enable the fungus to grow on a variety of different substrates such as lignocellulosic waste. In this study white rot fungi Pleurotus pulmonarius was tested for lignin peroxidase production in a submerged liquid fermentation. To enhance the enzyme production the influence of different parameter such as culture composition, inoculum size and agitation speed were investigated. The optimum cultivation condition for highest lignin peroxidase activity of 95.54± 2.26 U/ml was obtained in the presence of 1% (w/v) yeast, 1% (w/v) glucose and 1% (w/v) sawdust at agitation speed of 120 rpm and inoculum size of 2 discs. An aqueous two-phase system composed of recyclable random copolymer of ethylene oxide (EO)-propylene oxide (PO) and potassium phosphate salt was employed for the recovery of Pleurotus pulmonarius lignin peroxidase from submerged liquid fermentation. Lignin peroxidase partitioned in ATPS system was examined under various parameters such as polymer molecular weight, phase composition, volume ratio (VR), system pH and addition of sodium chloride. The result showed that the highest enzyme purification factor was achieved by ATPS composed of 18.80% (w/w) EOPO 3900, 7.11% (w/w) potassium phosphate with volume ratio of 0.82 at pH 7. Furthermore, the result showed that purification of lignin peroxidase is not influenced significantly by addition of sodium chloride. The purification factor of 9.22±1.07 and yield of 80.47% were achieved from the bottom phase of this optimized ATPS system with enzyme activity of 22.37±2.30 U/ ml. The recycling of EOPO was conducted at the end of recovery process. A recovery of more than 80% of the EOPO 3900 polymer was obtained from the ATPS. The result indicated that there is no significant difference in the purification factor and partitioning efficiency of purified lignin peroxidase in the ATPS system using fresh or recycled polymer.